The association between breast cancer and S100P methylation in peripheral blood by multicenter case–control studies. (25th January 2017) - Yang, Rongxi; Stöcker, Sarah; Schott, Sarah; Heil, Jörg; Marme, Frederik; Cuk, Katarina; Chen, Bowang; Golatta, Michael; Zhou, Yan; Sutter, Christian; Wappenschmidt, Barbara; Schmutzler, Rita; et al.
Summary: This study reveals significant association between blood-based decreased S100P methylation and BC, and provides another proof for the application of altered DNA methylation signatures from blood cells as potential markers for the detection of BC, especially for the early stage. Abstract: Breast cancer (BC) is the leading cancer in women worldwide. Changes in DNA methylation in peripheral blood could be associated with malignant diseases. Making use of screening results by llumina 27K Methylation Assay, we validated demethylation of five CpG sites of S100P gene in blood cell DNA of BC patients by three independent retrospective studies with subjects from different centers (Validation I: 235 familial BC case and 206 controls, odds ratio per −1% methylation > 1.03, and P < 6.00 × 10 –8 for all five CpG sites; Validation II: 189 sporadic BC case and 189 controls, odds ratio per −1% methylation > 1.03, P < 8.0 × 10 –5 for four CpG sites; Validation III: 156 sporadic BC case and 151 controls, odds ratio per −1% methylation > 1.03, P < 6.0 × 10 –4 for four CpG sites). In addition, the blood-based S100P methylation pattern was similar among BC patients with differential clinical characteristics regardless of stage, receptor status and menopause status. The observed BC-associated decreased S100P methylation in blood mainly originates from the leucocytes subpopulations but not B cells. The methylation levels of most S100P CpG sites were inversely correlated with the expression of S100P in leucocytes ( P < 1.2 × 10 –4 ) and in tissue ( P < 1.1 × 10 –4 ). This study reveals significant association between blood-based decreased S100P methylation and BC, and provides another proof for the application of altered DNA methylation signatures from blood cells as potential markers for the detection of BC, especially for the early stage.